2011
DOI: 10.1007/s10096-011-1444-2
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans serotypes infections and periodontal conditions: a two-way assessment

Abstract: This study investigated a large population of individuals positive for A. actinomycetemcomitans and performed a two way analysis assessing the relation between the different serotypes of the bacterium and periodontal conditions. The serotypes analysis (serotypes a, b, c, d, e, f) showed that out of the 204 selected individuals positive for A. actinomycetemcomitans, 152 were positive for a single serotype, 27 showed a variable mixed infection and 25 individuals were not positive for any of the serotypes tested.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
2
25
2
1
Order By: Relevance
“…In Brazil, an association between serotype b and healthy periodontium and between serotype c and chronic periodontitis was observed (22), differing from other data, which associated serotype b strains with patients with aggressive periodontitis (35). Aggressive periodontitis subjects were not exclusively associated with A. actinomycetemcomitans serotype b (31,35).…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…In Brazil, an association between serotype b and healthy periodontium and between serotype c and chronic periodontitis was observed (22), differing from other data, which associated serotype b strains with patients with aggressive periodontitis (35). Aggressive periodontitis subjects were not exclusively associated with A. actinomycetemcomitans serotype b (31,35).…”
Section: Discussioncontrasting
confidence: 70%
“…In Brazilian subjects, serotypes a, b and c were largely found (98%), and serotype c was the most prevalent. Serotypes d, e, and f were either not detected or relatively rare (22,31,35). The distribution pattern of A. actinomycetemcomitans serotypes in the subgingival plaque of subjects residing in the United States showed that serotype c is the dominant serotype, followed by serotypes a and b, and serotypes d, e, and f were either not detected or relatively rare (32).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Sobre la base de la antigenicidad del polisacárido-O componente del lipopolisacárido (LPS) bacteriano, en A. actinomycetemcomitans se han identificado seis serotipos diferentes: a-f (29)(30)(31) . Los serotipos de A. actinomycetemcomitans más frecuentemente detectados en la cavidad oral en humanos son a, b y c, siendo el serotipo b el detectado con mayor frecuencia en pacientes afectados de periodontitis agresiva (32) . En este contexto, la mayor frecuencia de detección del serotipo b de A. actinomycetemcomitans en pacientes con periodontitis agresiva sugiere un mayor potencial patogénico y este podría asociarse a una mayor inmunogenicidad y virulencia (33) .…”
Section: Introductionunclassified